Improving Students’ Vocabulary Mastery Through English Animation Movie - Ninin, Windi; Dollah, Syarifuddin; Muliati, Andi (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The purpose of this study was to find out whether or not the use of English animation movie improves students' vocabulary mastery. This study employed a quantitative approach with a pre-experimental design. The population of this study was students in class 8 at SMP Negeri 49 Makassar, and the sample was 29 students in class 8.1. Data were collected through pretest and posttest. The data were analyzed statistically using t-test at significant level 0.05. From the result of data analysis, the probability value (sig. 2-tailed) = 0.000 which is lower than the significance level of 0.05. The researcher found that H0 is rejected and H1 is accepted. Based on the result of data analysis, the researcher concluded that the use of English animation movie improved students’ vocabulary mastery at SMP Negeri 49 Makassar.Keywords: Vocabulary Mastery, Animation Movie.